2005
DOI: 10.1093/humrep/deh774
|View full text |Cite
|
Sign up to set email alerts
|

Simple enumerations of peripheral blood natural killer (CD56+ NK) cells, B cells and T cells have no predictive value in IVF treatment outcome

Abstract: There were no significant differences between simple enumerations of peripheral blood NK cells (including total CD56(+) NK, CD56(dim) NK and CD56(bright) NK cells), B cells and T cells with IVF treatment outcome and pregnancy outcome. Women who had a peripheral NK cell level >12% did not have higher number of previous pregnancy losses. Importantly their pregnancy rate was not reduced and their miscarriages were not increased compared to women who had a peripheral NK cells level <12%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 20 publications
3
35
0
1
Order By: Relevance
“…B lymphocytes express c-Myc proto-oncogene which can stimulate angiogenesis via production of VEGF [34]. However, there does not seem to be a significant difference between the number of endometrial B cells [35] or peripheral B cells [36] in women with normal obstetrical histories compared to those with a history of recurrent miscarriage undergoing IVF treatments.…”
Section: B and T Lymphocytesmentioning
confidence: 99%
“…B lymphocytes express c-Myc proto-oncogene which can stimulate angiogenesis via production of VEGF [34]. However, there does not seem to be a significant difference between the number of endometrial B cells [35] or peripheral B cells [36] in women with normal obstetrical histories compared to those with a history of recurrent miscarriage undergoing IVF treatments.…”
Section: B and T Lymphocytesmentioning
confidence: 99%
“…It has been found that in women with a history of RM, 37.3 % had a mild to moderate increase (12–18 %) and 14.7 % a marked increase (>18 %) in peripheral blood CD56 + NK cells. An NK cell percentage of <12 % is strongly associated with a subsequent successful pregnancy [20, 26]. However, these findings have not been confirmed by other studies that concluded that peripheral NK cell numbers do not necessarily correlate with NK cell cytotoxicity, which can be represented by markers such as KIRs (killer inhibitory receptors) or CD16 receptor expression [27].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also revealed a close correlation between an increased number of uterine NK cells (uNK) in the mid‐secretory phase and the occurrence of unexplained RM . The relationship between NK cells and pregnancy outcome as well as the associated mechanisms remains the subject of intense debate.…”
Section: Introductionmentioning
confidence: 99%